Peran Badan Perencanaan Pembangunan Daerah Dalam Menciptakan Effective Development di Kabupaten Ciamis - Febrianti, Adinda Ratna; Purnamasari, Syara; Garis, Regi Refian; Yuliani, Dini (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
The Regional Development Planning Agency is the government agency responsible for spatial planning and research. The main task of Bappeda is to assist Governors, Regents and Mayors to carry out research in the area of ​​regional government development planning. One important factor in the success of regional development planning is the existence of a competent institution or work unit, as well as a reliable information system to support it. Musrenbang is one way of implementing development in the regions where regional development planning functions as a guideline for development implementation and a benchmark for measuring regional development performance. The success of the development process was greatly helped by the existence of a Musrenbang communication system which included the Musrenbang as one of the media that could absorb people's aspirations. This research was conducted at the Regional Development Planning Agency of Ciamis Regency, with the object being development in Ciamis Regency where the purpose of this research was to find out the extent of the role of Bappeda of Ciamis Regency in regional development and to find out the inhibiting factors in carrying out coordination planning and implementation of development.